The Communication Patterns of Single Parent Families in Forming Children's Morals in Medan City - Suheri Suheri; Syukur Kholil; Lahmuddin Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to analyze the communication patterns of single parents in forming children's morals in Medan city, to analyze the application of single parent communication patterns in forming children's morals in Medan city and to analyze the moral development of children who have single parents in Medan city. This research is a descriptive qualitative approach. This method describes the state of the subject or object of research at this time based on facts that are visible or as they are. The results of the research conducted show the Communication Pattern of Parents in Forming Children’s Morals in the Medan City, namely: a. Authotarian pattern, this relationship pattern of parents is low in forming children's morals in Medan city, but the control is high, likes to punish physically, behave in a command, being stiff (hard), tends to be emotional and rejects the opinions of children. b. Permissive pattern, in this pattern the attitude of parents is high in shaping children's morals in Medan city, but the control is low, giving freedom to children, c. The authoritative pattern, in this pattern parents and their control are high in shaping children's morals in Medan city, being responsive to the needs of children, accepting children's opinions.